Brood Season Habitat Selection by Montezuma Quail in Southeastern Arizona - Kirby D. Bristow; Richard A. Ockenfels (National Quail Symposium Proceedings, 2017)
Habitat conditions during brood season can affect Montezuma quail (Cyrtonyx montezumae) population levels in Arizona, and land use practices can affect these habitat conditions. General habitat affinities of Montezuma quail are known, however, information on specific habitat selection patterns is limited. We investigated seasonal habitat selection by Montezuma quail in the foothills of the Huachuca and Santa Rita mountains in southeastern Arizona. We used pointing dogs to locate quail during brood seasons (Aug–Oct) of 1998 and 1999. We measured habitat components at 60 flush sites and 60 associated (100 m) random plots. Compared to random plots, quail used areas with higher grass and forb species richness, and more trees (P < 0.10). Low level (<= 50 cm) visual obstruction, usually associated with bunchgrass cover, was greater (P < 0.10) at flush sites than at random plots. Optimum brood season habitat for Montezuma quail should contain >= 6 species of forbs/0.01 ha, tree canopy cover between 10 and 50%, and grass canopy cover between 50 and 85% with a minimum average height of 25cm. Maintaining these habitat characteristics could minimize negative impacts of land-use practices on Montezuma quail.
Keywords: Arizona; Cyrtonyx montezumae; grazing; habitat selection; livestock; Madrean evergreen woodland; Montezuma quail